On the distribution of the peak-to-average power ratio in OFDM signals. - Ochiai, H.
The distribution of the peak-to-average power ratio (PAPR) in strictly band-limited orthogonal frequency-division multiplexing (OFDM) signals is studied. Assuming that the base-band OFDM signal is characterized as a band-limited complex Gaussian process, we first attempt to derive the exact distribution of the PAPR in the band-limited OFDM signals. Since this distribution cannot be expressed in a closed form, we further develop a simple closed-form approximation, based on the level-crossing rate analysis. Comparisons of the proposed distributions with those obtained by computer simulations show good agreement and convergence with an increase in the number of subcarriers
Keywords: PAPR distribution; Band-limited OFDM signals; Band-limited complex Gaussian process; Base-band OFDM signal; Closed-form approximation; Computer simulations; Convergence; Level-crossing rate analysis; Orthogonal frequency-division multiplexing; Peak-to-average power ratio; Subcarriers